Assessment of the urogynaecology patient in primary care and when to refer. Issue 2 (June 2020) - Basu, Maya
Urogynaecological symptoms are commonly encountered problems in women of post-reproductive age, which have a major impact on quality of life in affected women. This review summarises a standardised approach to common urogynaecological problems in primary care, which focuses on making the correct diagnosis, assessing impact, evaluating for other relevant lifestyle and medical factors and indications for referral into secondary care.